2023
DOI: 10.1021/acsmaterialslett.3c00379
|View full text |Cite
|
Sign up to set email alerts
|

Bright and Renal-Clearable Au Nanoclusters with NIR-II Excitation and Emission for High-Resolution Fluorescence Imaging of Kidney Dysfunction

Abstract: Real-time monitoring of kidney dysfunction in vivo is of great significance to the diagnosis of renal diseases and the preservation of human health, which can be achieved by second near-infrared (NIR-II) fluorescence imaging. However, the development of NIR-II fluorescence imaging for the study of kidney dysfunction has been impeded by a lack of renalclearable NIR-II luminescent materials with good optical properties. This study synthesized renally clear gold nanoclusters (Au NCs) with both NIR-II excitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Yi et al reported a new kind of renal-clearable dual-ligand-stabilized gold nanoclusters (AuNCs) by using mercaptohexanoic acid (MHA) and another thiolate such as cysteamine (Cystm), 2-mercaptoethanol (ME), or DL-dithiothreitol (DTT) as ligands (Figure ). The series of AuNCs with NIR-II excitation and emission, high quantum yield, and good photostability and biocompatibility can be capable of renal clearance and can be used for high-resolution FLI of renal ischemia-reperfusion (RIR) and unilateral ureteral obstruction (UUO) induced kidney dysfunction in vivo. Precious metal photothermal agents with plasmon-enhanced fluorescence effect have excellent photothermal effects and multimodal imaging capabilities and show great application prospects in PTT and tumor diagnosis and treatment.…”
Section: Types Of Photothermal Agents Commonly Used In Pttmentioning
confidence: 99%
See 1 more Smart Citation
“…Yi et al reported a new kind of renal-clearable dual-ligand-stabilized gold nanoclusters (AuNCs) by using mercaptohexanoic acid (MHA) and another thiolate such as cysteamine (Cystm), 2-mercaptoethanol (ME), or DL-dithiothreitol (DTT) as ligands (Figure ). The series of AuNCs with NIR-II excitation and emission, high quantum yield, and good photostability and biocompatibility can be capable of renal clearance and can be used for high-resolution FLI of renal ischemia-reperfusion (RIR) and unilateral ureteral obstruction (UUO) induced kidney dysfunction in vivo. Precious metal photothermal agents with plasmon-enhanced fluorescence effect have excellent photothermal effects and multimodal imaging capabilities and show great application prospects in PTT and tumor diagnosis and treatment.…”
Section: Types Of Photothermal Agents Commonly Used In Pttmentioning
confidence: 99%
“…(B) NIR-II FLI of RIR mice after intravenous injection of MHA/Cystm-AuNCs at different time points. Reprinted with permission from ref , copyright 2023 American Chemical Society.…”
Section: Types Of Photothermal Agents Commonly Used In Pttmentioning
confidence: 99%
“…mice was surgically ligated. [252,255,256] This procedure led to a marked decrease in blood perfusion and glomerular filtration rate, resulting in reduced entry of NCs into the obstructed kidney. However, the filtration and transport of these NCs from the bloodstream through the glomeruli to the cortex were not significantly delayed (Figure 16a,b).…”
Section: Metal Nc-biological Interactions Within the Dysfunctional Ki...mentioning
confidence: 99%
“…However, the development of NIR-II fluorescence bioimaging is in its infancy, and many fluorescent probes have relatively weak absorption and emission in the NIR-II window, resulting in poor imaging performance . To achieve high-performance NIR-II bioimaging, various materials with bright NIR-II emission have been extensively explored in the past few years and can be divided into two main categories: inorganic materials and organic materials. Since the pioneering research on the use of single-walled carbon nanotubes for in vivo NIR-II fluorescence imaging, an increasing number of inorganic NIR-II fluorescence materials, including rare earth nanoparticles, inorganic quantum dots, and gold nanoclusters, have been extensively used in NIR-II fluorescence biological imaging. Inorganic materials have relatively high quantum yields and low photobleaching sensitivity; however, practical clinical applications of these materials are still limited owing to concerns about biosafety and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%